GAPNING STRUKTURA TURLARI - ABDURAUF FITRAT TALQINIDA - Ashirboev, S. (SCIENCE and SOCIETY, 2022)
Abdurauf Fitrat, in his book "Nahv (syntax)" series "An Experiment on the Rules of the Uzbek Language", raised topical issues of Uzbek language syntax in his time. In this work, he put forward his views on the syntax of a phrase, a simple sentence, its syntactic parts, and the structural types of sentences: one- and two-part sentences, complete and incomplete sentences. Of course, this was due to the experience of his scientific life in St. Petersburg. This article discusses Abdurauf Fitrat’s system of complete and incomplete speech, with special emphasis on Fitrat’s terminology of these concepts. The source of the article is the 1927 edition of Nahv (Uzdavnashr).